Unit Testing Pada Aplikasi Web (Studi Kasus Bisnis Jasa Laundry) - Sanni Pramushinto; Novian Adhi Jaya; Azizah Azhaar; Muhammad Noviadih; Aries Saifudin (Shofanah Media Berkah, 2023)
Software testing is when we test a product or service to see how good it is in quality. Software testing is the process of examining software objectively and independently. This is useful for companies to know how risky the use of the software is before sending it to customers. Testing is done using white-box testing technique, which is considered a futile strategy because testing requires large resources. In this study, researchers used a black box approach because this test focuses on system functionality and functional requirements identified at the software analysis stage. The following objectives were set for the design of this system: • Designing a web application for laundry services using PHP. • Building a system that can store data in real time and facilitate the collection and processing of consumer, employee, supplier and asset information. • We provide facilities for billing and Accurate and structured event reporting. Testing of the laundry service web application system developed using the black box testing methodology shows that the system is able to display failed login notifications on the login menu, improve customer flow, and administrative and customer-specific dashboards with a normal Create test data display.